The Effect of External CSR on Customer Loyalty in Nepalese Banking Sector: Mediating Roles of Reputation, Satisfaction, and Trust - Danuwar, Ranjana Kumari; Chapagain, Bal Ram; Mahato, Surendra; Paudel, Udaya Raj (Journal of Business and Social Sciences Research, 2025)
Corporate Social Responsibility (CSR) is increasingly practised, with companies not only prioritizing profit growth but also contributing to society. Thus, this study examines the impact of external CSR on customer loyalty in Nepal’s banking sector, considering customer satisfaction, trust, and corporate reputation as mediating variables. This study uses explanatory research design, and data were collected from 403 bank’s customers in the Kathmandu Valley via Kobo Toolbox. Structural equation modelling (SEM) was applied to analyse relationships among the study variables. The results indicate that external CSR significantly enhances corporate reputation and customer satisfaction but has no direct impact on customer loyalty or trust. However, customer satisfaction positively influences trust. A key finding reveals that corporate reputation, customer satisfaction, and trust mediate the relationship between external CSR and customer loyalty. Additionally, awareness of CSR initiatives in the locality remains low. Respondents emphasised that banks should support local development by collaborating with municipalities to establish public amenities such as chautara (sitting areas), taps, and road maintenance. These insights help enhance customer loyalty and CSR effectiveness in Nepal’s banking sector.